Reconsidering Freud’s Dream Theory - Binswanger, Ralf; Wittmann, Lutz (International Journal of Dream Research, 2019)
This article aims at facilitating the understanding of Freud´s dream theory for psychoanalytic as well as non-psychoanalytic clinicians and scientists. The new perspective is based on a section of An Outline of Psychoanalysis (Freud, 1938) which, to date, does not appear to have been considered adequately. This section comprises a dense summary of Freud´s dream theory applying the structural viewpoint (ego, id and super-ego). It is suggested that this section be considered as akin to a set of explanatory notes for the reading of The Interpretation of Dreams (Freud, 1900), which is illustrated herein by applying it to several paragraphs of this work. In doing so, it becomes apparent that The Interpretation of Dreams does not need to be re-written in order to integrate the structural viewpoint. Rather, both the topographical (conscious, preconscious and unconscious) and the structural viewpoint can be elegantly merged. Finally, the introduced perspective is compared to previous psychoanalytic contributions and summarized straightforward.